Faktor-Faktor Yang Mempengaruhi Kejadian Hiperemesis Gravidarum Pada Ibu Hamil Di Puskesmas Kabanjahe Kab. Karo Tahun 2023 - Serinaenti Br Meliala; Kamelia Sinaga; Imran Saputra Surbakti; Agustina Susilawati Tumangger (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Hyperemesis gravidarum is excessive nausea and vomiting during pregnancy. This dangerous vomiting is differentiated from the normal morning sickness commonly experienced by pregnant women because its intensity exceeds normal vomiting and lasts during the first trimester of pregnancy. One complication as a direct result of pregnancy is hyperemesis gravidarum, where this complication can be detected and prevented regularly during pregnancy. Nausea and vomiting occur in 60-80% of Primigravida and 40-60% of Multigravida. In one in 1000 pregnancies these symptoms become more severe. This feeling of nausea is caused by increased levels of the hormones estrogen and hCG (human chorionic gonadotrophin) in the serum. The physiological influence of this increase in hormones is not clear, perhaps due to the central nervous system or insufficient gastric emptying. This hyperemesis can cause dehydration and hunger, the cause of which is unknown. Psychological factors can trigger or worsen vomiting. Weight loss and dehydration. Dehydration can cause changes in electrolyte levels in the blood so that the blood becomes too acidic. If vomiting continues, liver damage can occur. Another complication is bleeding in the retina caused by increased blood pressure when the sufferer vomits. Patients are treated and receive fluids, glucose, electrolytes and vitamins via IV. The general aim of this research is to find out what factors influence the incidence of hyperemesis gravidarum at the Kabanjahe District Health Center. Karo 2023. The type of research used is descriptive correlational with a cross sectional research design. The total population used was 36 people using purposive sampling technique. In collecting secondary and primary data. From the results of statistical tests using Chi-Square, it is known that the p-value is 0.021, so it can be concluded that there is a statistically significant relationship between maternal age and the incidence of hyperemesis gravidarum in pregnant women at the Kabanjahe District Health Center. Karo in 2023.